Informacje bibliograficzne na łamach czasopisma „Fides – Biuletyn Bibliotek Kościelnych” (1995-2015) - Gołda, Agnieszka (Archiwa, Biblioteki i Muzea Kościelne, 2017)
The article focuses on the issues of the semi-annual " Fides – Biuletyn Bibliotek Kościelnych" of the years1995-2015, published and made available online by the Federation of Church Libraries FIDES. One of the tasks of the founding body was the promotion of bibliographic activity. The author searched for bibliographic information in the journal in order to present how these objectives were accomplished. The article presents bibliographies concerning church libraries, bibliographies of journal content, biobibliographies and bibliographies of the internet texts. The author attempted to present the methodological assumptions of the lists and their subject matter